(untitled) - Sperling, L. H. (Hoboken, N.J., 2006)
This updated version of the classic, bestselling introductory textbook to physical polymer science emphasizes interrelationships between molecular structure and the morphology and mechanical behavior of polymers. It is an invaluable resource for professionals in polymer science, materials science, chemical engineering , and students of all levels
Keywords: Polyme,Polymers,Polymers,Polymers,Polymers